The Importance of Increasing Pancasila Awareness Among Students in the Campus Environment - Evriano, Reygil; Farhan Kamil; Meily Armi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Pancasila is the ideological, national and way of life of the Indonesian people which is expected to guide society in building social, national and state life to achieve national ideals. As a state ideology, Pancasila was not only created by the state, but is the result of extraction from the spiritual, moral and cultural riches of the Indonesian nation which have long been rooted in the beliefs and traditions of society. Therefor, Pancasila values are dynamic and continue to develop along with the social development of Indonesia society. These values are a solid basis for the life of society, nation and state, which cannot be separated and from a unifield whole. This research confirms that pancasila is not just the basic of the state, but is also a spiritual and cultural resource that regulates the life pf the Indonesian nation in a holistic and sustainable manner.